Performance Analysis of LTE system for 2x2 Rayleigh and Rician Fading Channel - Sah, Mithun; Chugh, Achint (Pandawan, 2021)
Development of LTE is a milestone in the field of communication engineering. Compared to the performance of 2G the network involving LTE provides much higher data rates and support much more services. The evolution to LTE has provided the users to utilize many commercial activities to bring forward to the public and provide them the improved services compared to older versions of communication technologies. As the growth of LTE has provided much faster network still there are improvements going on the new technology. Various performance measures have been taken into considerations has the networks has performed very well on such test. One of the performance analyses has been presented in this paper comparing the performance of the LTE system over the Rayleigh and Rician fading channel. In the paper the performance of the MIMO LTE has been analyzed for the networks with various modulation schemes for Rayleigh and Rician fading channel with a 2x2 MIMO channel for EPA 0Hz, EVA 5Hz, EVA 70Hz. By varying Signal to Noise Ratio (SNR), Bit Error Rate (BER) of LTE is calculated for different Multi-Input Multi-Output (MIMO) schemes. The analysis is concluded in terms of speed of the data rate in Mbps.